2022
DOI: 10.3390/cells11213372
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Induced Ketosis, Upregulated IGF-1/Insulin Receptors and the Canonical Insulin Signaling Pathway in Neurons, and Decreased the Excitatory Neurotransmitter Glutamate in the Brain of Non-Diabetics

Abstract: Sodium-glucose cotransporter-2 inhibitors (SGLT2is), such as empagliflozin, lower blood glucose in type 2 diabetes mellitus and improve cardiorenal outcomes regardless of diabetes presence. Whether SGLT2is exert any effects on the brain's metabolism has 6not been studied. We conducted a single-arm clinical trial to investigate the effects of once daily administration of oral empagliflozin (25 mg) for 14 days on systemic and brain metabolism in 21 non-diabetics aged 55 years old or older. Empagliflozin lowered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…This outcome can be attributed to the various properties of empagliflozin as an SGLT2 inhibitor, particularly its ability to inhibit the oxidative-inflammatory-apoptosis pathway, and other hormonal effects such as a decrease in serum ACTH levels. Additionally, empagliflozin has neurotransmitter effects such as reducing glutamate concentration [ 60 ]. To the best of our knowledge, this study is the first clinical trial that investigates the effect of add-on treatment of empagliflozin with its complex set of neuroreceptor, neuroinflammatory and neurohormonal effects on clinical depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome can be attributed to the various properties of empagliflozin as an SGLT2 inhibitor, particularly its ability to inhibit the oxidative-inflammatory-apoptosis pathway, and other hormonal effects such as a decrease in serum ACTH levels. Additionally, empagliflozin has neurotransmitter effects such as reducing glutamate concentration [ 60 ]. To the best of our knowledge, this study is the first clinical trial that investigates the effect of add-on treatment of empagliflozin with its complex set of neuroreceptor, neuroinflammatory and neurohormonal effects on clinical depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In microglia, scavenger receptor-related genes, such as macrophage scavenger receptor 1 ( Msr1 ) and CD36, are related to low-density Chol uptake [ 72 ], amyloid beta phagocytosis [ 80 ], and lipid metabolism homeostasis [ 81 ]. In microglia and astrocytes, fatty acid oxidation-related genes, such as Ppara and Pgc1a , are associated with autophagy, neuronal proliferation, memory formation [ 82 , 83 ], microglia polarization [ 84 ], and apoptosis [ 85 ]. In astrocytes, glutamate transporter-related genes, such as Gls , are related to excitatory neurotransmitter secretion and synapse transmission [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, a recent report of >11,000 cases with T2D and dementia compared with >46,000 T2D controls found that SGLT2i treatment was associated with a 42% reduced risk of dementia, the largest effect of any anti‐diabetic medication 44 . A recent open label study in cognitively normal older non‐diabetic adults also showed that empagliflozin reduced cerebral glutamate levels assessed with magnetic resonance spectroscopy, and acutely increased markers of insulin signaling in neuronal origin‐enriched extracellular vesicles 46 …”
Section: Other Metabolic Modulators: Sglt2 Inhibitorsmentioning
confidence: 99%